Faktor-faktor yang mempengaruhi ekspor pala Indonesia ke Vietnam - Novidayanti, Vivi; Hodijah, Siti; Mustika, Candra (e-Journal Perdagangan Industri dan Moneter, 2019)
The purpose of this study was to analyze the factors that influence Indonesia's nutmeg exports to Vietnam, with the variables of exchange rates, international prices, and Vietnam's gross domestic product. The data analysis method used is descriptive and quantitative methods, the data analysis tool used is the OLS (Ordinary Least Square) method. Includes annual data for 38 years, with secondary data sourced from the Directorate General of Plantations, Bank Indonesia, and the World Bank as research objects. The data analysis technique is multiple linear regression, partial hypothesis testing using the t-test, and simultaneously using the F-test with a significant level of 5%. Based on the results, it can be concluded that partially the exchange rate (NT) has a positive and significant effect on export volume (VE); international price (HI) has a negative and significant effect on export volume (VE), and Vietnam's gross domestic product (GDP) has a positive and significant impact on the export volume (VE) of Indonesian nutmeg. Keywords: Export volume, Exchange rate, International price, Gross domestic product.